Relationship between myofascial pain and facial types: an observational study - da Silva, Francisco Ferreira; Barroso, Mayra Soares Ferreira; Guimarães, Antônio Sérgio; Valadas, Lidia Audrey Rocha; Rodrigues, Luciane Lacerda Franco Rocha (Brazilian Dental Science, 2023)
Temporomandibular disorder (TMD) is a term that covers a number of clinical problems involving the masticatory muscles, TMJ and all associated structures leading to signs and symptoms such as jaw pain, otalgia, headaches and limitation of function. In this context, TMD has been related to facial type and there are three distinct facial types (euryprosopic, mesoprosopic, and leptoprosopic). Objective: The aim of this study was to investigate the correlation between myofascial pain and facial types classified by the RDC/TMD Axis I. Material and Methods: this study was composed of 64 women aged between 12 and 49 years, using data obtained from two institutions. We used the anthropometric methodology, which meets the criteria of simplicity and reliability. We also applied the Brugsh Facial Index. The individuals were classified as euryprosopic (51.56%), mesoprosopic (12.50%) and leptoprosopic (35.94%), without statistical significance among the groups (p=0,3492). Results: there is no statistical difference between the age groups (p=0.2976) and no association between facial type and age range. Conclusion: this study found that there was a correlation between myofascial pain and facial types, with the predominance of euryprosopic faced women aged between 20 and 29 years when compared with other facial types and other age groups. KEYWORDS Temporomandibular joint dysfunction syndrome; Anthropometric methodology; Mandibular disorders; Myofascial pain; Orofacial pain.